Diversity of Zooplanktons in Betna Wetland, Belbari, Morang - Tiwari, R.B.; Thapa Chhetry, D. (Our Nature, 2010)
This paper deals with the diversity of zooplanktons in Betna Wetland, Morang Key words: Zooplankton, taxonomic groups, Betna wetland DOI: 10.3126/on.v7i1.2580 Our Nature (2009) 7:236-237